The role of positive spirituality in preventing child maltreatment and promoting resilience: a perspective on policy and practice - Van Tuyll Van Serooskerken Rakotomalala, Sabine; Anis, Katy; Hillis, Susan; Tucker, Sydney; Li, Xiaoan; Stok, Marijn (Frontiers in Public Health, 2025)
Child maltreatment remains a pervasive global issue with profound impacts on health, development, and societal well-being. While evidence-based strategies for violence prevention have expanded, the role of spirituality as a protective and rehabilitative factor remains underexplored in mainstream policy and practice. This perspective article examines how nurturing spiritual values across the life course—such as empathy, emotional regulation, and ethical decision-making—can contribute to violence prevention and resilience building. Drawing on recent empirical findings and global policy examples, the paper argues for the integration of positive spirituality into child protection and faith-based initiatives across home, school, and community settings. The article outlines actionable strategies for practitioners and policymakers, highlights culturally responsive measurement tools, and calls for strengthened collaboration between child protection and faith-based sectors. By advancing a holistic and values-based approach to caregiving, this perspective contributes to ongoing efforts to disrupt intergenerational cycles of violence and promote children’s well-being in low-, middle-, and high-income countries worldwide.